Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-23 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Comparison between the development of an infant and repair of a cervical spinal cord injury upon CDT. Left penal, positioning upon 0.5 years of therapy and right penal after 5 years of therapy.